Narasi Pastoral dan Kritik Ekologi Dalam Ontologi Cerpen Temukan Warna Hijau Yang Diprakarsai Reni Erina (Kajian Ekokritik Sastra) - Randa Anggarista (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2020)
This research aims to identify form of pastoral narative and ecological criticism in the short story ontology of Temukan Warna Hijau initiated by Reni Erina with using perspective of ecocriticism. This research is a qualitative research using descriptive analysis method. The data in this research are the form of text that refers to formulation of problem about the form of pastoral narratives and ecological criticism in short story ontology of Temukan Warna Hijau, while the data source in this research is short story ontology of Temukan Warna Hijau initiated by Reni Erina and published by PT Elex Media Komputindo at 2014. The data collection technique was done by reading and writing techniques, while the data analysis technique was carried out through the stages of identification, classification, interpretation, and conclusion. The instrument in this research is writer oriented to research on form of pastoral narratives and ecological criticism. Based on result of research, in short stories ontology of Temukan Warna Hijau, was found in presence of pastoral narratives (environmental wisdom) shown by the figures, such as affection and concern for nature, respect for nature, and an attitude of responsibility towards nature. In addition, in the short stories ontology of Temukan Warna Hijau also found ecological criticism in the form of river acosystems pollution, extinction of living things in an ecosystem, and illegal logging.